Hubungan Antara Gaya Belajar, Kemandirian Belajar, dan Minat Belajar dengan Hasil Belajar Biologi Siswa - Nurlia Nurlia; Yusminah Hala; Rachmawaty Muchtar; Oslan Jumadi; Mushawwir Taiyeb (Jurnal Pendidikan Biologi, 2017)
The students’ learning results in Biology are influenced by two factors, namely internal and external factors. The internal factors that can influence learning results are learning style, learning independence, and learning interest. The research aims to discover the relation of  learning style, learning independence and learning interest with Biology learning results of the students at SMAN 1 Tonra in Bone District.The research is ex post facto. The population of the research were the students of class IPA at SMAN 1 Tonra in Bone District of academic year 2016/2017. The samples were 194 students taken by using stratified random sampling technique. Data were collected by employing questionnaire and documentation. The data of the research were analyzed by using descriptive and inferential statistics techniques. The results of the research reveal that (i) the students’ learning style tends to be in visual type, (ii) the students’ learning independence is in high category, (iii) the students’ learning interest is in high category, (iv) the students’ Biology learning results is in high category, (v) there is strong relation between learning style and the students’ Biology learning results, (vi) there is fairly strong relation between learning independence and the students’ Biology learning results, (vii) there is strong relation between learning interest and the students’ Biology learning results, and (viii) there is very strong relation between learning style, learning independence, and learning interest toword Biology learning results of the students at SMAN 1 Tonra in Bone District.